2016
DOI: 10.1002/adma.201506305
|View full text |Cite
|
Sign up to set email alerts
|

Giant Hysteresis of Single‐Molecule Magnets Adsorbed on a Nonmagnetic Insulator

Abstract: metal electrode. We use nonmagnetic, insulating MgO, wellknown in inorganic spintronic applications, [ 17,18 ] which allows to control the electron tunneling rate over many orders of magnitude. [ 19 ] Moreover, we employ the TbPc 2 SMM [ 14,15,[20][21][22][23] as a model system. In the neutral molecule, the Tb(III) ion exhibits an electronic spin state of J = 6. It is sandwiched between two phthalocyanine (Pc) macrocycles (cf. schematic view in Figure 1 a) hosting an unpaired electron delocalized over the Pc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
194
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 159 publications
(216 citation statements)
references
References 32 publications
14
194
2
Order By: Relevance
“…In addition, it has been demonstrated that the divalent state of Tb is highly unfavorable even for freestanding dimers, i.e., a single metallic bond is sufficient to trigger its trivalent configuration [48]. Hence, a Tb atom on graphene takes on the most common trivalent configuration that is also observed for TbPc 2 molecular magnets [43,49].…”
Section: Trivalent Re Atoms On Graphene/ir(111)mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, it has been demonstrated that the divalent state of Tb is highly unfavorable even for freestanding dimers, i.e., a single metallic bond is sufficient to trigger its trivalent configuration [48]. Hence, a Tb atom on graphene takes on the most common trivalent configuration that is also observed for TbPc 2 molecular magnets [43,49].…”
Section: Trivalent Re Atoms On Graphene/ir(111)mentioning
confidence: 97%
“…The magnetic relaxation time has been reported to depend on x-ray photon flux [17,42,43]. This effect is due to the generation of secondary electrons that destabilize the magnetic quantum states.…”
Section: Flux Dependence Of Dy Magnetization Curvesmentioning
confidence: 99%
“…Ab-initio models have been routinely employed to predict which ligand environments allow for the best optimisation of the spin relaxation times [49][50][51], in view of fabricating molecular devices that could store and process information above cryogenic temperatures. Recent work has made significant gains in this direction, with reports of slow magnetic relaxation at temperatures as high as 100 K and magnetic blocking at 5-30 K in Dy- [32][33][34][35][36], Er- [52,53] and Tb- [54,55] SIMs. Other notable achievements are the observation of Rabi oscillations in f-element single molecules [56][57][58][59], and the detection of 'atomic clock transitions' in a Ho-SIM system [60].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the XMCD sum rules [38,39] and multiplet analysis can be used to estimate the corresponding J z values. We chose late lanthanides for their large magnetic moments coming from the parallel alignment of L and S. Additionally, they exhibit larger magnetic anisotropy and have been more intensively studied as model systems for atomic magnetic memories in single ion [40][41][42][43] and single atom magnets [17,18]. Among the series of late lanthanides, we investigated Dy, Ho, Er, and Tm as they have been found both in divalent and trivalent states in bulk compounds [44], hence, they represent ideal candidates to explore the interplay between surface binding, 4f occupancy, and strength of the crystal field.…”
Section: Introductionmentioning
confidence: 99%